The Role of Professional Ethics of Religious Counselors in Preventing Religious Polarization and Encouraging Moderate Behavior - Majid, Asmarani; Rahmawati, Rahmawati (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study examines the role of professional ethics of religious counselors in preventing religious polarization and promoting moderate religious behavior within society. Employing a qualitative field research approach, the study was conducted in the working area of Islamic religious counselors in Tamalanrea District. Data were collected through in-depth interviews, participatory observation, and documentation, involving religious counselors as key informants, supported by community leaders and assisted communities. Data analysis was carried out using qualitative techniques through data reduction, data presentation, and inductive conclusion drawing, with data validity ensured through source and method triangulation. The findings reveal that the consistent implementation of professional ethics such as honesty, objectivity, inclusivity, social responsibility, and respect for diversity serves as a fundamental foundation for religious counseling practices. Professional ethics enable religious counselors to deliver religious messages in a persuasive, dialogical, and contextual manner, thereby reducing exclusivist narratives and preventing the emergence of religious polarization. Moreover, ethical professionalism strengthens the role of religious counselors as moral exemplars, social mediators, and facilitators of intergroup dialogue, which significantly contributes to the internalization of moderate (wasathiyah) religious behavior. This study concludes that strengthening the professional ethics of religious counselors is a strategic necessity for maintaining religious harmony, reinforcing social cohesion, and enhancing socio-religious resilience in Indonesia’s plural and multicultural society.